A validated chemiluminescence immunoassay for methotrexate (MTX) and its application in a pharmacokinetic study. Issue 1 (30th November 2015) - Song, Zhaorui; Wang, Yufen; Dong, Yaqing; Xu, Kun; Long, Hao; Deng, Chuan; Yin, Yongmei; Eremin, Sergei A.; Meng, Meng; Xi, Rimo
Abstract : Polyclonal antibodies for anticancer drug methotrexate (MTX) were originally produced, and a chemiluminescence immunoassay was developed for plasma MTX determination. Abstract : For routine monitoring of the pharmacokinetic behavior of anticancer drug methotrexate (MTX), polyclonal antibodies for MTX were originally produced, and a sensitive chemiluminescence immunoassay (CLIA) was developed for the determination of plasma MTX. Three kinds of coupling reagents (EDC, CDI and isobutyl chloroformate) were utilized to synthesize MTX immunogens. The coupling ratio, titer and sensitivity of polyclonal antibodies for each immunogen were evaluated. Consequently, MTX–EDC–cBSA was found to be the optimal immunogen since it showed the highest coupling ratio and yielded antibodies with the highest sensitivity. Under optimal conditions, the developed CLIA showed a limit of detection (LOD) of 4.3 ng mL −1 in buffer and 9.1 ng mL −1 in plasma with acceptable coefficients of variations (<14.9%). The method exhibited no cross-reaction with the MTX metabolite (7-OH MTX) and structural analogs. When applied in a pharmacokinetic study, the CLIA results were statistically consistent with the HPLC method in measuring key pharmacokinetic parameters ( t 1/2, C max, AUC0–12 and MRT0–12 ). In conclusion, the CLIA method showed advantages of simple sample preparation, low cost, high sensitivity and good reproducibility. These properties make it a potential tool in the rapid detection of MTX for therapeutic drug monitoring (TDM).